Maintenance of Cera Tanks and Bucket Elevators to Streamline the Unloading Process on Cement Carrier MV. Oceanic Success - Purba, Damoyanto; Baihaqi Baihaqi; Moh. Iskandar Rafi Zulkarnain (Dinasti Publisher, 2022)
Cement is one of the most important building materials in the world of construction today. So that the demand for cement can be used as a benchmark in the implementation of development in a country. Cement ship unloading equipment is very influential on the availability of cement supply both in Indonesia and the world. Damage to the unloading equipment on the cement carrier ship, especially the Cera Tank and Bucket Elevator, has an impact on the delay in the loading and unloading process at the port. So that maintenance is very important in order to avoid the delay in loading and unloading. This research was conducted in MV. Oceanic Success for 12 months. The aim is to find out things that must be considered in terms of maintenance of cement carrier ship unloading equipment. This research method uses a qualitative descriptive method with data analysis techniques, namely Root Cause Analysis with the help of the 5 Why Analysis Method tool. The results of this study indicate that the Cera Tank and Bucket Elevator unloading tools are lacking in terms of maintenance. Thus causing delays in the unloading process on the MV ship. Oceanic Success.